1987
DOI: 10.1038/330773a0
|View full text |Cite
|
Sign up to set email alerts
|

Electron transfer from protein to DNA in irradiated chromatin

Abstract: Irradiation of dry or fully hydrated frozen DNA systems (conditions of direct damage) has been shown by electron-spin resonance spectroscopy to give rise to electron-gain centres localized on thymine (T.-) and electron loss centres ('holes') localized on guanine (G.+) with approximately equal yields. Our parallel studies on the development of both single- and double-strand breaks under comparable conditions provide good evidence that these radical centres are the precursors to such damage, and we and others ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(28 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…The effects of the direct ionization of DNA, however, are less likely to be inhibited by the folding of the chromatin. On the contrary, there are indications that radiation energy deposited in the proteins of chromatin may be transferred to the DNA, thus compounding the DNA-damaging consequences of the direct effect of ionizing radiation [37]. Alternatively, the difference seen in "native" and compact chromatin could reflect an inability of the Fe(ll)-EDTA complex to penetrate these chromatin structures.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of the direct ionization of DNA, however, are less likely to be inhibited by the folding of the chromatin. On the contrary, there are indications that radiation energy deposited in the proteins of chromatin may be transferred to the DNA, thus compounding the DNA-damaging consequences of the direct effect of ionizing radiation [37]. Alternatively, the difference seen in "native" and compact chromatin could reflect an inability of the Fe(ll)-EDTA complex to penetrate these chromatin structures.…”
Section: Discussionmentioning
confidence: 99%
“…35 In this context, amino acids having oxidation potentials less than that of guanine (1.29 V at pH 7) that can transfer one electron to guanine in a favorable manner are of paramount importance. 35,36 The occurrence of such reactions has already been observed by the flash-quench technique, 37 ESR, 38 pulse radiolysis, 39 and other experimental 36,40,41 studies.…”
Section: Introductionmentioning
confidence: 89%
“…Possible explanations are: mtDNA is located close to the ROS producing OXPHOS and mtDNA lacks protective histones [81,82]. However, there is a debate about the protective role of histones, as there is also evidence showing that the electrons can transfer easily from histones to DNA leading to damage [83] and under some conditions (exposure to Cu(II)/H 2 O 2 ) histones can even enhance DNA damage [84]. It is also suggested that DNA-binding proteins of mitochondrial nucleoids can be as equally protective as histones for mtDNA under H 2 O 2 or X-ray exposure [85,86].…”
Section: Mtdna Characteristicsmentioning
confidence: 96%